The Effect of Financial Inclusion on Inclusive Economic Growth in Indonesia - Ayu Az Zahra, Della; Ajija, Shochrul Rohmatul (Jurnal Ilmu Ekonomi Terapan, 2023)
This study examines the influence of financial inclusion on inclusive economic growth in Indonesia using data from 34 provinces. Financial inclusion is measured using the number of bank branch offices, the ratio of credit savings to GRDP, and third-party funds. Meanwhile, economic growth is described by the logarithmic variable of the difference in GRDP per capita. Secondary data from the Central Statistics Agency (BPS) and the Financial Services Authority (OJK) are used in this study. According to the statistical panel regression estimation results, the savings ratio per GRDP and third-party funds significantly positively affect inclusive economic growth. In contrast, the number of bank branch offices has no significant effect on inclusive economic growth.